The Effectiveness of Mindfulness-Based Cognitive Behavioral Therapy on Anxiety and Emotion Regulation in Adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD) - Hajizeynali, Narges (Iranian Journal of Neurodevelopmental Disorders, 2025)
Article type: Original Research How to cite this article: Atri, R., Shafizadeh, H., & Soleimani, N. (2025). The Effectiveness of Mindfulness-Based Cognitive Behavioral Therapy on Anxiety and Emotion Regulation in Adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD). Iranian Journal of Neurodevelopmental Disorders, 4(1), 64-72. https://doi.org/10.61838/kman.jndd.4.1.8 © 2025 the authors. Published by Iranian Association for Intelligence and Talent Studies, Tehran, Iran. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0) License. Purpose: The aim of the present study was to examine the effectiveness of mindfulness-based cognitive behavioral therapy (MB-CBT) on anxiety and emotion regulation in adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD). Methods and Materials: This research was applied in nature and employed a quasi-experimental design with a pre-test–post-test format, including a control group and random assignment of participants. The statistical population consisted of all adolescents aged 12–16 with ADHD who visited the Rah-e-No Counseling Center in District 3 of Tehran in 2024. Using purposive sampling, 30 adolescents were selected and assigned to the experimental group (n = 15) and the control group (n = 15). The experimental group underwent ten 60-minute sessions of mindfulness-based cognitive behavioral therapy, while the control group did not receive any treatment. Data were collected using the Anxiety Inventory (Beck et al., 1988) and the Emotion Regulation Questionnaire (Garnefski & Kraaij, 2006). The data obtained from the questionnaires were analyzed using SPSS version 27 in both descriptive and inferential sections (ANCOVA). Findings: The results indicated that mindfulness-based cognitive behavioral therapy led to a significant reduction in anxiety and an increase in positive emotion regulation. Conclusion: These findings suggest that MB-CBT can be considered an effective intervention for reducing anxiety and improving emotion regulation in adolescents diagnosed with ADHD.